Social and Economic Opportunities and Challenges of Plant-Based and Cultured Meat for Rural Producers in the US - Newton, Peter; Blaustein-Rejto, Daniel (Frontiers in Sustainable Food Systems, 2021)
Animal agriculture presents major sustainability challenges. Alternative meat (alt-meat) products (e.g., plant-based and cultured meat) are substitutes for animal meat products, made using innovative food technologies. The potential environmental impacts of plant-based and cultured meat have been well-explored but the social and economic impacts of alt-meat have received less attention, particularly as they relate to rural communities. This paper addresses the research question: What are social and economic opportunities and challenges of cultured and plant-based meat for rural producers in the US? We conducted semi-structured interviews with 37 expert informants, including representatives of cultured meat companies, plant-based meat companies, non-profit organizations, funding agencies, governmental agencies, and the beef, soy, and pea sectors, as well as researchers and farmers. Our interviews revealed a range of ways in which alt-meat sectors might present opportunities or threats for rural producers in the US. Opportunities included growing crops as ingredients for plant-based meat or feedstock for cultured meat; raising animals for genetic material for cultured meat; producing cultured meat in bioreactors at the farm level; transitioning into new sectors; new market opportunities for blended and hybrid animal- and alt-meat products; and new value around regenerative or high-animal welfare farming. Threats included loss of livelihood or income for ranchers and livestock producers and for farmers growing crops for animal feed; barriers to transitioning into emerging alt-meat sectors; and the possibility of exclusion from those sectors. Interviewees also identified a range of roles for universities and research organizations, government agencies, and non-profit organizations that could help to maximize the benefits and minimize the risks from emerging alt-meat sectors. Finally, most interviewees thought it likely that alt-meat would form an additional form of protein that captured some or all of the anticipated growing demand for protein rather than one that displaced animal meat entirely. As such, the emergence of alt-meat sectors alongside animal agriculture may offer more choices for rural producers in terms of which markets they sell to and what forms of production they adopt or pursue. This paper identifies numerous research gaps, to which natural and social scientists could usefully apply their attention.